Cost of Medications Recommended by Canadian Acne Clinical Practice Guidelines. Issue 6 (November 2016) - Czilli, Tiffany; Tan, Jerry; Knezevic, Sanja; Peters, Colin
Background: Acne affects a large proportion of the Canadian population and has psychosocial and financial consequences. Objective: We provide cost information for treatments recommended by the Canadian acne guidelines. Methods: Highest level recommendations were selected for 3-month usage cost. Results: Three-month estimated treatment costs were as follows: topical retinoids ($14.40-$73.80), benzoyl peroxide (BPO; $6.75), fixed-dose BPO-clindamycin ($40.95-$44.10) and BPO-adapalene ($73.80), oral antibiotics ($25.20 for tetracycline 250 mg qid; $52.20 and $52.74 for doxycycline 50 mg bid and 100 mg od, respectively), and hormonal therapy ($26.46-$37.80 for ethinyl estradiol [EE] 0.030 mg/drospirenone 3mg and $75.60-108.99 for EE 0.035 mg/cyproterone acetate 2 mg). Oral isotretinoin 3-month costs ranged from $393.96 to $478.80. Conclusions: Awareness of costs of recommended treatments may facilitate improved outcomes by increasing procurement and adherence.